THE IMPACT OF ORGANIZATIONAL CULTURE, HUMAN RESOURCE QUALITY, MOTIVATION, AND DISCIPLINE ON EMPLOYEE PERFORMANCE IN CLASS IIA CORRECTIONAL INSTITUTION BOJONEGORO, EAST JAVA, INDONESIA - Arizka Wahyu Pratama; Kuswandi Kuswandi; Sri Rahayu (ITB AAS Indonesia Surakarta, 2024)
The objective of this study is to analyze the impact of organizational culture, human resource quality, motivation, and discipline on employee performance. This quantitative research utilized a saturated sample of all 61 officers at the Class IIA Bojonegoro Correctional Institution. Data collected through Google Form questionnaires was analyzed using the SPSS 25.0 software. Findings revealed that organizational culture and motivation do not significantly affect employee performance, whereas human resource quality and discipline do. This study aims to bridge the gap by investigating the correlation between organizational culture, human resource quality, motivation, discipline, and employee performance in correctional facilities. It is anticipated that this research will enhance our understanding of the factors influencing employee performance in correctional institutions and contribute significantly to the advancement of knowledge in the field of human resource management.